The 50th anniversary of the Cahn-Ingold-Prelog specification of molecular chirality - Helmchen, Günter (Angewandte Chemie. International edition, 2016)
“… Just over 50 years ago, Robert S. Cahn, Sir Christopher Ingold, and Vladimir Prelog published the Review ‘Specification of Molecular Chirality’ in Angewandte Chemie. The article would change the everyday language of the chemist by bringing the term chirality to their attention. Today, the CIP system is the specification tool in organic chemistry …” Read more in the Editorial by Günter Helmchen.
Gesehen am 12.05.2020